# Why does this grammar derive into $\beta \alpha ^*$ instead of $\alpha ^* \beta$?

In this video clip the teacher presents a grammar $A \rightarrow A \alpha | \beta$ and after providing the parse tree explains that the regular expression for the language generated is represented as $\beta \alpha ^*$.

Why isn't it $\alpha ^* \beta$ instead? Isn't the grammar left-recursive into terminal $\alpha$ and once terminal $\beta$ is reached the string ends?

Try some derivations:

• $A\Rightarrow \beta$
• $A\Rightarrow A\alpha\Rightarrow \beta \alpha$
• $A\Rightarrow A\alpha\Rightarrow A\alpha\alpha\Rightarrow \beta \alpha\alpha$

The pattern is clear: starting from $A$, we'll generate strings of the form $\beta\alpha\dotsc\alpha$, in other words, $\beta\alpha^*$. Since at any stage we have $A$ on the left of the sentential form, we'll eventually generate strings with $\beta$ on the left.

If the grammar had been $A\rightarrow \alpha A\mid \beta$, then we'd derive strings of the form $\alpha^*\beta$.

• Ok I get it now. Because we continue to derive the $A$ until we reach $\beta$ and terminate the derivation, so $A$ cannot derive to $\alpha$ without further recursion. I was reviewing a note from a while back and had forgotten that. Thanks.
– Dave
Dec 3 '16 at 18:43